Aspectos petrofísicos de sedimentos de dunas na região de Natal-RN - Aguiar, Renan Silva (2019)
This work continues as a continuation of the studies of the Group of Physical Properties of Rocks of the Department of Geophysics-UFRN. A granulometric analysis of ten well selected and unconsolidated real samples was performed. The granulometric bands were determined from sieving tests performed in the laboratory. Soon after the selection, using a microscope, images of selected particles were generated. Then, using Image J software, the diameters of 100 grains were measured for each sample. Thus, the mean diameters were determined by the logarithmic scale and arithmetic scale, being the first one more suitable for Sedimentology studies. Histograms were made to visualize grain distribution, presenting curves close to log-normal. After grading, the porosity and permeability tests were performed for the later phase. The porosity measurements for each sample were performed by a Helium gas porosimeter. Although the samples were well selected for porosity, a greater constancy was expected in the average porosity of the grains. Since in the literature, for well-selected samples, the porosity does not vary in relation to grain size, already in the present study, it showed just the opposite. In the last step of the present study, permeability measurements were made with the samples with a variable charge permeameter. With the flow time marked at the time of the tests, we determined the hydraulic conductivity and permeability.